Academic Disagreement in Australian Urban Research: An Introspective Analysis. Issue 3 (3rd July 2018) - Bervoets, Wouter; Gleeson, Brendan
ABSTRACT: This commentary aims at a better understanding of academic disagreement through an introspective analysis of its nature within the Australian urban research community. The academic debate on urban consolidation was used as a case study. The analysis shows that the force with which urban scholars promulgate their opposing standpoints is strengthened by a broad set of subjective value judgements. Academic disagreements are further enhanced by the social interactions of researchers and the heterogeneous social processes and circuits of scientific activity. The commentary concludes by discussing how a reflexive embrace of academic disagreement by urban scholars could give rise to more constructive and impactful debate and policy application.